ALAT DESTILASI SEDERHANA SEBAGAI MEDIA EDUKASI UNTUK MENINGKATKAN MINAT WIRAUSAHA SISWA-SISWI SMA IT AL KAMAL NW NARMADA - Dina Asnawati; Saprini Hamdiani; I Made Sudarma; Nurul Ismilayli (Jurnal Pijar Mipa, 2015)
Abstrak: Peningkatan Sumber Daya Manusia dalam pelaksanaannya menghadapi banyak kendala terutamaÃÂ  dalamÃÂ  halÃÂ  saranaÃÂ  danÃÂ  prasaranaÃÂ  terutamaÃÂ  bagiÃÂ  sekolah-sekolahÃÂ  swastaÃÂ  diÃÂ  pedesaan LombokÃÂ  Barat.ÃÂ  SalahÃÂ  satunyaÃÂ  adalahÃÂ  SMAÃÂ  ITÃÂ  AlÃÂ  KamalÃÂ  NWÃÂ  NarmadaÃÂ  yangÃÂ  terletakÃÂ  diÃÂ  Desa Golong Kecamatan Narmada, Lombok Barat. Sekolah yang berdiri tahunÃÂ  2008 ini belum memiliki fasilitasÃÂ  ruangÃÂ  danÃÂ  alatÃÂ  laboratorium.ÃÂ  HalÃÂ  iniÃÂ  sangatÃÂ  menyulitkanÃÂ  siswaÃÂ  untukÃÂ  dapatÃÂ  memahami konsep-konsepÃÂ  IPAÃÂ  secaraÃÂ  lebihÃÂ  mendalamÃÂ  tanpaÃÂ  disertaiÃÂ  praktikum.ÃÂ  SehinggaÃÂ  perluÃÂ  dilakukan inovasiÃÂ  denganÃÂ  memanfaatkanÃÂ  barang-barangÃÂ  bekasÃÂ  yangÃÂ  mudahÃÂ  diperolehÃÂ  untukÃÂ  dijadikanÃÂ  alat peragaÃÂ  sederhana.ÃÂ  SalahÃÂ  satuÃÂ  inovasiÃÂ  yangÃÂ  telahÃÂ  dilakukanÃÂ  adalahÃÂ  perancanganÃÂ  danÃÂ  pembuatan sendiriÃÂ  alatÃÂ  praktikumÃÂ  destilasiÃÂ  sederhana,ÃÂ  untukÃÂ  membantuÃÂ  siswaÃÂ  memahamiÃÂ  konsepÃÂ  destilasi serta penerapannya dalam industri. Diharapkan pengabdian ini akan meningkatkan kreatifitas dan minatÃÂ  paraÃÂ  siswa/siswiÃÂ  SMAÃÂ  ITÃÂ  AlÃÂ  KamalÃÂ  untukÃÂ  mengembangkanÃÂ  penggunaanÃÂ  alatÃÂ  destilasi sederhana tersebut dalam bidang praktis seperti pertanian sehingga dapat juga menigkatkan jiwa kewirausahaan siswa.Kata kunci : alat destilasi sederhana, praktikum, wirausahaAbstract: ImprovementÃÂ  ofÃÂ  humanÃÂ  resourcesÃÂ  facesÃÂ  manyÃÂ  challenges,ÃÂ  especiallyÃÂ  inÃÂ  termsÃÂ  of facilities and infrastructure, especially for private schools in rural, West Lombok. One of the high schools that face the same problem is the High School IT Al Kamal NW Narmada located in the villageÃÂ  ofGolongÃÂ  DistrictÃÂ  ofÃÂ  Narmada,ÃÂ  LombokÃÂ  Barat.ÃÂ  SchoolÃÂ  wasÃÂ  establishedÃÂ  inÃÂ  2008ÃÂ  butÃÂ  have no adequateÃÂ  classroomÃÂ  facilitiesÃÂ  andÃÂ  laboratoryÃÂ  equipment.ÃÂ  ItÃÂ  isÃÂ  veryÃÂ  difficultÃÂ  forÃÂ  studentsÃÂ  to understandÃÂ  scienceÃÂ  conceptsÃÂ  inÃÂ  moreÃÂ  depthÃÂ  withoutÃÂ  laboratoryÃÂ  workÃÂ  activity. ThereforeÃÂ  itÃÂ  needs innovationÃÂ  forÃÂ  simpleÃÂ  laboratoryÃÂ  workÃÂ  activityÃÂ  byÃÂ  utilizingÃÂ  second-handÃÂ  goodsÃÂ  thatÃÂ  readilyavailable.ÃÂ  TheÃÂ  simpleÃÂ  innovationÃÂ  thatÃÂ  hasÃÂ  beenÃÂ  introducedÃÂ  isÃÂ  toÃÂ  designÃÂ  andÃÂ  manufactureÃÂ  simple distillationÃÂ  apparatusÃÂ  inÃÂ  orderÃÂ  toÃÂ  helpÃÂ  studentsÃÂ  understandÃÂ  theÃÂ  conceptÃÂ  ofÃÂ  distillationÃÂ  andÃÂ  its applicationÃÂ  inÃÂ  theÃÂ  industry.ÃÂ  ThisÃÂ  approachÃÂ  isÃÂ  expectedÃÂ  toÃÂ  increaseÃÂ  creativityÃÂ  andÃÂ  interestÃÂ  ofÃÂ  the student especially from SMA IT Al Kamal to develop simple destilation apparatus for practical purposes (e.g in agriculture) so that it is espected that student has entrepreneurs skills.ÃÂ Keywords :simple distillation device,ÃÂ  laboratory work, entrepreneur